Spherical alumina particles, method for producing same, and resin composite composition containing same
Through freeze-drying or airflow heating and drying technology, the problem of residual sodium ions and high cohesion on the surface of alumina particles is solved, and the production of spherical alumina particles with low Na concentration and low cohesion is achieved, avoiding poor curing and crushing pollution.
Patent Information
- Application Number
- CN202380068477.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-10-02
- Publication Date
- 2025-05-02
AI Technical Summary
In the existing alumina production methods, the residual sodium ions on the surface of the product will lead to poor curing of the resin and loss of voltage resistance. At the same time, the alumina particles have high cohesion and need to be broken and contaminated.
By freeze-drying or air-flowing heating of the alumina slurry, the sodium ions freeze and particle agglomeration caused by long-term heating are avoided, and directly dried into powdered products.
The production of spherical alumina particles with low surface residual Na concentration and low cohesion is achieved, and problems such as poor curing, loss of voltage resistance and crushing pollution are avoided.
Smart Images

Figure CN119923371A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to spherical alumina particles, and in particular to spherical alumina particles having a reduced surface residual Na concentration and a low degree of aggregation, a method for producing the same, and a resin composite composition containing the spherical alumina particles. Background Art
[0002] In recent years, due to the high functionality and high speed of electronic devices such as mobile phones, the heat generated by the electronic components inside the electronic devices has increased. In order for the electronic devices to work properly, it is an important issue to release the generated heat to the outside efficiently. Those used for heat dissipation are called heat sinks and heat dissipation adhesives. They are attached or coated and crimped between the heating element and the heat dissipation fins, so that the gap between the heating element and the heat dissipation fins can be eliminated and the heat can be dissipated efficiently. In addition, the semiconductors inside the electronic components themselves also generate significant heat due to the same high functionality and high speed, and the sealing materials that protect the semiconductors are also required to have heat dissipation properties.
[0003] Generally, heat sinks, heat dissipation adhesives, and semiconductor sealing materials are composed of thermally conductive inorganic fillers and resins. The thermally conductive inorganic fillers use raw materials such as inexpensive aluminum hydroxide, aluminum oxide (hereinafter referred to as alumina), and silicon carbide, boron nitride, and aluminum nitride that are expected to have high thermal conductivity. In particular, aluminum oxide is often used as a thermally conductive inorganic filler because it is inexpensive and chemically stable.
[0004] Prior Art Literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-21710
[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-120673 Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] The Bayer process is widely known as a method for producing aluminum oxide. In the Bayer process, aluminum oxide is dissolved as sodium aluminate by treating bauxite with caustic soda (sodium hydroxide), and impurities such as iron, titanium, and silicon are precipitated as red mud. The filtrate is filtered, and hydrous aluminum oxide Al is added to the filtrate (sodium aluminate solution). 2 O 3 ·3H 2 O seeds and stirred for several days to precipitate hydrous alumina in the liquid and recover it. By calcining the recovered hydrous alumina, high-purity alumina Al can be obtained. 2 O 3 .
[0010] In the Bayer process, since caustic soda (sodium hydroxide) is used for treatment, sodium may sometimes remain in the aluminum oxide of the product. If sodium is present in large quantities on the surface of the filler, it reacts with moisture in the resin and air to release hydroxide ions. The hydroxide ions react with the epoxy groups present in the epoxy resin to hinder the polymerization reaction between the resins, which is the cause of poor curing. In addition, if sodium ions and potassium ions are present in the resin composition prepared by mixing with the epoxy group, the voltage resistance is impaired. From the above aspects, the less the amount of sodium, the better. In order to remove or reduce the sodium, the aluminum oxide is dried after being washed with water.
[0011] Patent Document 1 discloses an apparatus capable of efficiently washing, filtering and drying a powder such as aluminum oxide in the same container. More specifically, it is suggested that by introducing compressed gas into the container, the powder can be washed, filtered and dried in the same container without the need for stirring blades in the device. In addition, it is disclosed that heating using electricity or steam, microwave irradiation and the like can be used to increase the drying speed.
[0012] As described above, when drying the washed alumina slurry, heat drying is mostly performed. However, due to the long-term heating during the heat drying process, the sodium ions remaining inside the alumina move to the outside and may be dissolved on the surface of the alumina that has been cleaned by washing. In addition, the smaller the particle size of the alumina particles contained in the slurry, the more the particles agglomerate with each other through heat drying, and the dried product becomes a firm agglomerate. Since it becomes an agglomerate, it needs to be crushed for powderization. Along with the crushing, foreign matter (contamination) from the crusher may be mixed into the alumina powder that becomes the product.
[0013] In addition, Patent Document 2 discloses a micro-particle spherical alumina powder, which uses micro-particle low-alkali alumina as a raw material, with a maximum particle size of 7 μm or less and an average particle size in the range of 0.2 to 0.9 μm. It is disclosed that the powder is subjected to a strong crushing treatment before the raw material powder is introduced into the flame, and the agglomerated particles are fully crushed and dispersed, and then continuously introduced into the flame immediately, so that a spherical inorganic oxide powder without coarse particles and with an average particle size of less than 1 μm can be stably obtained. However, as in Patent Document 1, foreign matter (contamination) from the crusher may be mixed into the alumina powder that becomes the product due to crushing. In addition, the concentration of the sodium component of the powder is not disclosed.
[0014] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide spherical alumina particles having a low surface residual Na concentration and a low degree of aggregation, a method for producing the same, and a resin composite composition containing the spherical alumina particles.
[0015] Technical means for solving technical problems
[0016] The present inventors dried the washed alumina slurry by a predetermined method and found that the slurry can be directly dried and powdered without crushing.
[0017] Based on the above findings, the gist of the present invention is as follows.
[0018] [1] A spherical aluminum oxide particle,
[0019] Its average particle size is 0.4-1.9um and its specific surface area is 1.0-5.0m 2 / g, the residual Na on the surface is less than 20ppm, containing Na 2 O is 1000 ppm or less, the degree of agglomeration is 1.0% or less, and the circularity is 0.9 or more.
[0020] [2] The spherical alumina particles according to [1], characterized in that
[0021] The alpha conversion rate is 10.0% or less.
[0022] [3] A method for producing spherical alumina particles, comprising:
[0023] A water slurry preparation step of mixing raw material spherical aluminum oxide with water to prepare a water slurry containing the raw material spherical aluminum oxide; and
[0024] A drying step of drying the water slurry.
[0025] [4] The method for producing spherical alumina particles according to [3],
[0026] The method includes a raw material spherical alumina washing step of washing the raw material spherical alumina with water before the water slurry preparing step.
[0027] [5] A resin composite composition, characterized in that:
[0028] Contains the spherical alumina particles described in [1] or [2].
[0029] [6] The resin composite composition according to [5],
[0030] It also contains at least one inorganic filler selected from amorphous spherical silica particles, crystalline spherical silica particles, titanium dioxide particles, magnesium oxide particles, aluminum nitride particles, boron nitride particles, barium titanate particles, calcium titanate particles, and carbon fibers.
[0031] Effects of the Invention
[0032] According to the present invention, spherical alumina particles having a low residual Na concentration on the surface and a low degree of cohesion and a resin composite composition containing the spherical alumina particles can be obtained. Since the residual Na concentration on the surface of the spherical alumina particles is low, when used as a filler, poor curing and loss of voltage resistance can be avoided. In addition, since the degree of cohesion is small, crushing is not required, and the mixing (contamination) of foreign matter caused by crushing can be avoided. Furthermore, according to the manufacturing method as one embodiment of the present invention, the spherical alumina particles can be easily manufactured. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a diagram schematically showing the state of aluminum oxide particles in the case of conventional heat drying and in the case of freeze drying according to the present embodiment. DETAILED DESCRIPTION
[0034] [Spherical alumina particles]
[0035] (Average particle size)
[0036] The average particle size of the spherical alumina particles as one embodiment of the present invention is 0.4 to 1.9 μm. If the average particle size is less than 0.4 μm, the agglomeration of the particles becomes greater, and the fluidity of the resin composition when used as a filler is significantly reduced, so it is not preferred. If the average particle size exceeds 1.9 μm, the particles will get stuck in the narrow part of the mounting substrate and the chip in the semiconductor packaging that is becoming smaller and thinner, and sometimes the fluidity of the liquid sealing material becomes worse and the moldability is reduced.
[0037] Here, the average particle size refers to the average particle size (D50), which means the median particle size D50 at which the cumulative volume is 50% in the volume-based particle size distribution measured by the laser diffraction / scattering particle size distribution measurement method. In addition, the laser diffraction / scattering particle size distribution measurement method is a method of irradiating a dispersion liquid in which spherical aluminum oxide particles are dispersed with laser light and obtaining the particle size distribution based on the intensity distribution pattern of the diffraction / scattered light emitted from the dispersion liquid. In the present invention, the laser diffraction / scattering particle size distribution measurement device used is "Mastersizer 3000 (manufactured by Malvern Co., Ltd.)". In addition, the average particle size of the raw material of the spherical aluminum oxide particles can also be obtained in the same manner.
[0038] (Specific surface area)
[0039] In one embodiment of the present invention, the specific surface area of the spherical alumina particles measured by the BET method is 1.0 m 2 / g above 5.0m 2 / g or less.
[0040] If the specific surface area of spherical particles is less than 1.0 m 2 / g, the particles are difficult to form a dense packing structure, so the fluidity of the liquid sealing material containing the particles may decrease. On the other hand, if the specific surface area of the spherical particles exceeds 5.0 m 2 / g, the tendency of particles to aggregate increases, and similarly, the fluidity of the liquid sealing material may decrease.
[0041] The specific surface area is measured by the BET method. Typically, the specific surface area is measured according to the following steps.
[0042] The measurement was performed by collecting about 5 g of sample and vacuum drying it at 250°C for 5 minutes. Then, the sample was placed in an automatic specific surface area measuring device (Macsorb, manufactured by Mountech), and the nitrogen adsorption amount at a relative pressure P / P0 of 0.291 was measured at a measuring temperature of 77K using pure nitrogen and nitrogen-helium mixed gas (mixing ratio of nitrogen 30% and He 70%), and the BET specific surface area was calculated by the one-point method.
[0043] (Surface residual Na)
[0044] In one embodiment of the present invention, the residual Na on the surface of the spherical alumina particles is 20 ppm or less. The residual Na on the surface here refers to Na adhering to and remaining on the surface of alumina, and is measured by ion chromatography.
[0045] If sodium is present in a large amount on the filler surface, i.e., the aluminum oxide surface, it reacts with the moisture in the resin and the air and releases hydroxide ions. The hydroxide ions react with the epoxy group present in the epoxy resin and hinder the polymerization reaction of the resins each other, becoming the reason for poor solidification. In addition, if sodium ions and potassium ions are present in the resin combination made by mixing with the epoxy group, the voltage resistance is impaired. If sodium is below 20ppm, poor solidification and the loss of voltage resistance can be avoided. From the above viewpoint, sodium is more preferably lower, but the cost burden of removing completely is large, so it is set to more than 0.1ppm.
[0046] The sodium remaining on the surface is measured by ion chromatography. Typically, the measurement is performed according to the following steps.
[0047] Add 4 g of sample and 40 ml of distilled water to a centrifuge tube, cover it, and shake it thoroughly to mix. After mixing, use a centrifuge to separate the sample and sample solution. Take the sample solution and analyze the sodium ion using ion chromatography. Ion chromatography is measured using an ion chromatograph manufactured by East Asia Medical Electronics.
[0048] (Contains Na 2 O)
[0049] In one embodiment of the present invention, the spherical alumina particles contain Na 2 O is less than 1000 ppm.
[0050] Here, the Na 2 O is the total amount of Na components present on the surface and inside of aluminum oxide, which is quantified as Na as oxide by atomic absorption spectrometry. 2 O.
[0051] If there is a large amount of Na in alumina 2 O, sodium exists not only on the surface of alumina but also inside. When alumina is heated, the sodium component is released to the particle surface, and the residual Na on the surface may increase. 2 O is below 1000ppm, the sodium content is low, and the free amount to the particle surface can be reduced. 2 The lower the O content, the better. However, since complete removal is difficult in terms of production management, the lower limit may be 50 ppm or more.
[0052] Contains Na 2 The method for measuring O is as follows: Regarding the amount of sodium oxide contained in the aluminum oxide particles, a person skilled in the art can use a known elemental analysis method, for example, an atomic absorption spectrometer, to convert the amount into oxides.
[0053] (Cohesion)
[0054] In one embodiment of the present invention, the degree of aggregation of the spherical alumina particles is 1.0% or less.
[0055] The degree of aggregation referred to herein is an index of whether particles are aggregated, and is measured by a measurement method utilizing sieving.
[0056] By heating and drying the washed slurry of aluminum oxide, the particles agglomerate to form larger blocks. Due to the agglomeration, crushing is required to separate the particles. Crushing leads to equipment wear and increased costs caused by contact with the crushing device. In addition, since the particles agglomerate to each other and are not dispersed sufficiently into the resin, the fluidity and viscosity of the resin composition may also deteriorate. If the degree of agglomeration is less than 1.0%, it means that there are fewer blocks, which means that crushing operation is not required. From the above viewpoint, the lower the degree of agglomeration, the better, but it is difficult to completely prevent agglomeration, so its lower limit can also be above 0.0001%.
[0057] The method for measuring the degree of cohesion is as follows.
[0058] Overlap two standard sieves with mesh sizes of 4.75 mm and 212 μm in sequence. The order of overlapping is to place the sieve with mesh size of 212 μm at the bottom and overlap it with mesh size gradually becoming larger. Place 50 g of sample on the top sieve with mesh size of 4.75 mm and set it on a vibrating sieve machine. The vibrating sieve machine used is OCTAGON200 manufactured by Endecotts. After setting the sieve, set the vibrating sieve machine to an amplitude of 5 and an oscillation time of 3 minutes. After the oscillation is completed, measure the particle weight of the particles remaining on each sieve and the particles passing through the mesh size of 212 μm. When the amount of particles on the mesh size of 4.75 mm is set as Ag, the amount of particles on the mesh size of 212 μm is set as Bg, and the amount of particles passing through the mesh size of 212 μm is set as Cg, calculate (cohesion degree) = A / (B+C)×100(%).
[0059] (Circularity)
[0060] In one embodiment of the present invention, the circularity of the spherical alumina particles is 0.90 or more. The higher the circularity of the spherical particles, the lower the viscosity of the resin composite composition containing the alumina particles, and the better the moldability. The circularity may be 0.91 or more, 0.92 or more, or 0.93 or more. The upper limit of the circularity is theoretically 1.0, but from the perspective of manufacturing management, it may be 0.98 or less or 0.95 or less.
[0061] The circularity can be measured using an electron microscope or an optical microscope and an image analysis device. For example, FPIA manufactured by Sysmex Corporation, etc. These devices are used to measure the circularity of particles (the circumference of the equivalent circle / the circumference of the projected image of the particle). The circularity is measured for more than 100 particles, and the average value is used as the circularity of the powder.
[0062] (α-ratio)
[0063] In one embodiment of the present invention, the alpha conversion rate of the spherical alumina particles may be 10.0% or less.
[0064] Here, the alpha conversion rate refers to the proportion of α-alumina crystals in the crystalline phase. Alumina is known to be crystalline, and α-alumina, θ-alumina, and δ-alumina are known as typical crystalline forms. The details of the spherical alumina particles of one embodiment of the present invention will be described later, but it can be produced based on a melt-blowing method in which the raw material is put into a flame to melt it and then quenched. In this case, the amorphous proportion of the obtained alumina can be increased, and spherical alumina particles with an alpha conversion rate of less than 10.0% can be easily obtained. The upper limit of the alpha conversion rate can be 5.0%, 3.0%, or 1.0%. The lower limit of the alpha conversion rate is not particularly limited, and it can also be 0.0%, but from the perspective of the burden of manufacturing management and the thermal conductivity characteristics of the resin composite composition, it can also be 0.1% or 0.4%.
[0065] The alpha conversion rate is measured using a powder X-ray diffraction device. The integral area of the obtained diffraction peak is calculated, and for the total, the ratio of the diffraction peak area from α-alumina is analyzed by the Rietveld method. Specifically, the X-ray diffraction pattern is obtained in the range of 2θ of 10° to 90° using D2PHASER manufactured by Bruker. The alpha conversion rate of the obtained pattern is calculated by the Rietveld method using DIFFRAC.TOPAS manufactured by Bruker. When calculating, it is assumed that only three crystalline phases, α-alumina, δ-alumina, and θ-alumina, are present for analysis, and the content of α-alumina is calculated.
[0066] (purity)
[0067] The purity of aluminum oxide in the aluminum oxide fine particles is preferably 99.99% or more and 100.00% or less. When the purity of aluminum oxide is less than 99.99%, the aluminum oxide particles tend to have irregular shapes.
[0068] As a specific example of an apparatus for measuring the purity of aluminum oxide particles, an analysis apparatus such as ICP emission analysis or AES, SIMS, which can quantify the impurity level with high sensitivity, can be used. The amount of impurities in the aluminum oxide particles of this embodiment is determined by ICP emission analysis and atomic absorption spectrometry. In addition, the determination is performed for each metal oxide according to the following JIS standard determination method.
[0069] ·Fe 2 O 3 (%): sulfuric acid (1+3) pressurized acid decomposition, ICP method
[0070] (JIS R 1649)
[0071] ·SiO 2 (%): Sodium carbonate-boric acid melting, ICP method
[0072] (JIS H 1901)
[0073] ·Na 2 O(%): sulfuric acid (1+3) pressurized acid decomposition, atomic absorption spectrometry
[0074] (JIS R 1649)
[0075] The purity of the aluminum oxide particles was calculated by the following formula: The purity was defined as a value rounded off to the third decimal place.
[0076] The purity of alumina particles [Al 2 O 3 (%)]=
[0077] 100(%)-[Fe 2 O 3 (%)]-[SiO 2 (%)]-[Na 2 O(%)]
[0078] [Method for producing spherical alumina particles]
[0079] In one embodiment of the present invention, a method for producing spherical alumina particles is provided. The method is a method for preferably producing the above-mentioned alumina particles, and includes the following steps.
[0080] (1) Manufacturing process of raw material alumina.
[0081] (2) A step of spheroidizing raw material alumina to produce raw material spherical alumina.
[0082] (3) a step of preparing a water slurry by mixing the raw material spherical alumina with water to prepare a water slurry containing the raw material spherical alumina; and
[0083] (4) A drying step of drying the water slurry.
[0084] (Raw material alumina)
[0085] As a method for producing raw material alumina, a thermal decomposition method of ammonium aluminum carbonate, a gas phase oxidation method, a deflagration method, a Bayer process, a hydrolysis method of aluminum alkoxide, or the like is used.
[0086] (Raw material spherical alumina)
[0087] The raw alumina can be spheroidized by a flame melting method to obtain raw spherical alumina.
[0088] The flame melting method is a well-known melt-blowing method, in which particles are sprayed into a flame to spheroidize the particles. At this time, the average sphericity can be adjusted by the amount of fuel gas fed into the flame per unit time. In addition, the particle size of the spherical alumina powder can be adjusted by adjusting the particle size of the particles used. There is no particular restriction on the refrigerant, but from the viewpoint of not reducing the purity of the spherical particles, gases such as air, nitrogen, and argon with few impurities and low activity are preferred.
[0089] In addition, raw material spherical alumina can also be produced by the deflagration method. The deflagration method is specifically as follows: a chemical flame is formed by a burner in an oxygen-containing atmosphere, and an amount of metal aluminum powder that forms a dust cloud is added to the chemical flame to cause deflagration to obtain spherical alumina particles.
[0090] (Water slurry)
[0091] The raw material spherical alumina is mixed with water to prepare a water slurry containing the raw material spherical alumina. From the viewpoint of not reducing the purity of the spherical particles, the water used for mixing is preferably distilled water or ion-exchanged water that does not contain sodium ions, chloride ions, etc. as impurities. The mixing amount can be appropriately adjusted in consideration of the viscosity of the slurry, etc.
[0092] (Cleaning)
[0093] Before the water slurry preparation step, a raw material spherical alumina washing step of washing the raw material spherical alumina with water may also be performed. The washing water, like the slurry water, may also be distilled water or ion exchange water that does not contain sodium ions, chloride ions, etc. as impurities. Alternatively, a cleaning agent or surfactant may be used for cleaning, depending on the object to be removed by cleaning. By appropriately adjusting the cleaning temperature, number of times, time, and other conditions, the alumina particles can be brought into the desired cleaning state. Typically, the desired surface residual Na concentration and Na content can be obtained. 2 O concentration. After washing, dehydration can also be performed using a filter or the like until an arbitrary particle concentration is reached. By dehydrating, the Na component or cleaning agent dissolved in the water can be rinsed off, thereby preventing re-adhesion after drying. In addition, water can be further added to the raw material spherical alumina after washing to dissolve the residual impurity components in water. When water is added, the impurity components attached to the surface of the alumina particles can be rinsed off by dehydrating again. In addition to high purification, by controlling the particle concentration to an arbitrary value, the efficiency of drying in the subsequent process can be improved.
[0094] (dry)
[0095] In order to take out the spherical alumina from the water slurry containing the raw material spherical alumina, the water is dried and removed. In the past, the drying was carried out by heating the static slurry for a long time so that the water evaporated from the slurry. At this time, as the heating progresses, the water in the slurry evaporates and decreases, so the distance between the alumina particles in the slurry becomes narrower. When the water is completely separated from the slurry, the alumina particles are in contact with each other and sometimes form a firm agglomerate. Furthermore, by heating the slurry for a long time, the sodium component moves from the inside of the spherical alumina particles contained in the slurry to the surface, and sometimes becomes free on the surface of the particles. In this regard, in the present embodiment, the water slurry containing the raw material spherical alumina is subjected to airflow heating drying or freeze drying.
[0096] (Freeze Drying)
[0097] In freeze drying, water is fixed by freezing, and the alumina particles are also fixed. Through freeze drying, water gradually leaves the system (slurry) due to sublimation, but since the alumina particles are fixed, the distance between the alumina particles is maintained to a certain extent, and contact and aggregation are suppressed. That is, when the drying is completed and the water is completely separated from the slurry, the contact between the alumina particles is minimized, and aggregation is difficult to occur. Figure 1 This is a diagram schematically showing the state of aluminum oxide particles in the case of conventional heating and drying and in the case of freeze drying in the present embodiment. As described above, when freeze drying in the present embodiment is performed, the aggregation of the obtained aluminum oxide particles is suppressed, and there is no need to break up the agglomerated masses of aluminum oxide particles. Generally, a crushing device such as a mill is used to break up the agglomerates, and there is a possibility of foreign matter mixing (contamination) from the crushing device. However, in the present embodiment, since crushing is not required, the mixing (contamination) of foreign matter caused by crushing is of course suppressed. Furthermore, since the heating temperature is low (10 to 90°C, more preferably the upper limit is 80°C), the seepage of the sodium component from the inside of the particles is limited to a minimum, so the amount of free sodium that re-attaches to the surface of the dried powder is reduced.
[0098] (Airflow Heating Drying)
[0099] In airflow heating drying, the slurry is sprayed into a high-temperature airflow of 100 to 300°C to evaporate only the water, thereby extracting the spherical alumina powder from the slurry. The slurry is sprayed into a high-temperature airflow using a nozzle such as a two-fluid nozzle. The sprayed slurry becomes fine droplets due to the dispersion effect in the airflow. Compared with the conventional heating drying method, the airflow heating drying method has a very large surface area by using a nozzle to make the slurry into droplets. Since the heat received by the slurry is proportional to the surface area of contact between the heat source and the slurry, the water in the droplets evaporates and dries in an instant. Compared with the conventional heating drying method, since the drying time is short (about 0.01 seconds to 10 seconds), the seepage of the sodium component from the inside of the particles is suppressed to a minimum, so the sodium that is free and re-attached to the dried powder is reduced. Furthermore, since the spherical alumina powder is sprayed into the airflow, the aggregation of the spherical alumina powders is suppressed, and there is no need to break up the agglomerated masses of alumina particles.
[0100] [Resin composite composition]
[0101] According to one embodiment of the present invention, a composite composition of spherical alumina particles and a resin can be produced. The composition of the resin composite composition is described in detail below.
[0102] The slurry composition containing spherical alumina particles and a resin can be used to obtain a resin composite composition such as a semiconductor sealing material (especially a solid sealing material) and an interlayer insulating film. Furthermore, by curing these resin composite compositions, a resin composite such as a sealing material (cured body) and a semiconductor packaging substrate can be obtained.
[0103] When manufacturing the resin composite composition, for example, in addition to the spherical alumina particles and the resin, a curing agent, a curing accelerator, a flame retardant, a silane coupling agent, etc. are added as needed, and the composite is prepared by a known method such as kneading. Then, the composite is formed into a granular form, a film form, etc. according to the application.
[0104] In addition, when manufacturing the resin composite composition, in addition to the spherical alumina particles and the resin, other inorganic fillers may be mixed. Examples of the inorganic filler include amorphous spherical silica particles, crystalline spherical silica particles, titanium dioxide particles, magnesium oxide particles, aluminum nitride particles, boron nitride particles, barium titanate particles, calcium titanate particles, and carbon fibers. The mixing ratio of the inorganic filler may be appropriately adjusted according to the purpose of the resin composite composition.
[0105] Furthermore, when the resin composite composition is cured to produce a resin composite, for example, the resin composite composition is melted by applying heat, processed into a shape corresponding to the application, and completely cured by applying heat higher than that when melted. In this case, a known method such as transfer molding can be used.
[0106] For example, in the case of manufacturing semiconductor-related materials such as a substrate for packaging or an interlayer insulating film, as the resin used in the resin composite composition, a known resin can be used, but an epoxy resin is preferably used. The epoxy resin is not particularly limited, and for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, naphthalene type epoxy resin, phenoxy type epoxy resin, etc. can be used. One of these can be used alone, or two or more with different molecular weights can be used in combination. Among them, from the viewpoints of curability, heat resistance, etc., an epoxy resin having two or more epoxy groups in one molecule is preferred. Specifically, there can be mentioned: biphenyl type epoxy resin, phenol novolac type epoxy resin, o-cresol novolac type epoxy resin, epoxy resin obtained by epoxidizing novolac resin of phenol and aldehyde, glycidyl ethers such as bisphenol A, bisphenol F and bisphenol S, glycidyl acid epoxy resin obtained by reaction of polyacids such as phthalic acid or dimer acid with epichlorohydrin, linear aliphatic epoxy resin, alicyclic epoxy resin, heterocyclic epoxy resin, alkyl modified multifunctional epoxy resin, β-naphthol novolac type epoxy resin, 1,6-dihydroxynaphthalene type epoxy resin, 2,7-dihydroxynaphthalene type epoxy resin, bishydroxybiphenyl type epoxy resin, and epoxy resin introduced with halogen such as bromine for imparting flame retardancy, etc. Among these epoxy resins having two or more epoxy groups in one molecule, bisphenol A type epoxy resin is particularly preferred.
[0107] In addition, resins other than epoxy resins can also be used as resins used in resin composite compositions for purposes other than composite materials for semiconductor sealing materials, such as prepregs for printed circuit boards, various engineering plastics, etc. Specifically, in addition to epoxy resins, polyamides such as silicone resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyimides, polyamide-imides, and polyetherimides; polyesters such as polybutylene terephthalate and polyethylene terephthalate; polyphenylene sulfide, aromatic polyesters, polysulfones, liquid crystal polymers, polyethersulfones, polycarbonates, maleimide-modified resins, ABS resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins can also be cited.
[0108] As a curing agent for the resin composite composition, a known curing agent can be used to cure the resin, for example, a phenolic curing agent can be used. As the phenolic curing agent, phenol novolac resin, alkylphenol novolac resin, polyvinylphenol, etc. can be used alone or in combination of two or more.
[0109] The phenolic curing agent is preferably blended in an equivalent ratio (phenolic hydroxyl equivalent / epoxy equivalent) of 0.1 or more and less than 1.0 to the epoxy resin. This eliminates the residual unreacted phenolic curing agent and improves the moisture absorption heat resistance.
[0110] From the viewpoint of heat resistance and thermal expansion coefficient, the amount of the spherical alumina particles added to the resin composite composition of the present invention is preferably large, and is usually appropriately 70% to 95% by mass, preferably 80% to 95% by mass, and more preferably 85% to 95% by mass. This is because if the amount of the spherical alumina particles is too small, it is difficult to obtain the effects of improving the strength of the sealing material and inhibiting thermal expansion. On the contrary, if it is too much, regardless of the surface treatment of the spherical alumina particles, it is easy to cause segregation caused by the aggregation of the spherical alumina particles in the composite material, and the viscosity of the composite material is also too large, so it is difficult to be used as a sealing material.
[0111] In addition to the resin, additive materials such as a silane coupling agent, a curing agent, a colorant, a curing delay material, and other known additives may be used.
[0112] Moreover, as the silane coupling agent, a known coupling agent may be used, but a silane coupling agent having an epoxy functional group is preferred.
[0113] A heat sink, heat dissipation paste, and the like can be obtained using a slurry composition containing spherical alumina particles and a resin.
[0114] When obtaining the heat sink, in addition to the spherical alumina particles and the resin, an additive is appropriately mixed and compounded by a known method such as kneading. The obtained composite is formed into a sheet by a known method.
[0115] For example, in the case of manufacturing a heat sink, as the resin used in the resin composite composition, a known resin can be used, specifically, polyamides such as silicone resin, phenolic resin, melamine resin, urea-formaldehyde resin, unsaturated polyester, fluororesin, polyimide, polyamide-imide, polyetherimide, etc.; polyesters such as polybutylene terephthalate and polyethylene terephthalate; polyphenylene sulfide, aromatic polyester, polysulfone, liquid crystal polymer, polyether sulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin. Among them, silicone resin is preferably used. The silicone resin is not particularly limited, for example, peroxide curing type, addition curing type, condensation curing type, ultraviolet curing type, etc. can be used.
[0116] In addition to the resin, additive materials such as a silane coupling agent, a curing agent, a colorant, a curing delay material, and other known additives may be used.
[0117] When obtaining the heat dissipation paste, in addition to the spherical alumina particles and the resin, an appropriate additive is added and compounded by a known method such as kneading. Here, the resin used in the heat dissipation paste is also referred to as a base oil.
[0118] For example, in the case of manufacturing thermal paste, as the resin used in the resin composite composition, known resins can be used, specifically, polyamides such as silicone resin, phenolic resin, melamine resin, urea-formaldehyde resin, unsaturated polyester, fluororesin, polyimide, polyamide-imide, and polyetherimide; polyesters such as polybutylene terephthalate and polyethylene terephthalate; polyphenylene sulfide, aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, mineral oil, synthetic hydrocarbon oil, ester oil, polyethylene glycol oil, silicone oil, fluoro oil, etc.
[0119] In addition to the resin, additives such as silane coupling agents, colorants, thickeners, and other known additives may be used. Thickeners may be calcium soaps, lithium soaps, aluminum soaps, calcium complex soaps, aluminum complex soaps, lithium complex soaps, barium complex soaps, bentonite, urea, PTFE, sodium terephthalate, silica gel, organic bentonite, and other known thickeners.
[0120] Example
[0121] The present invention will be described below with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.
[0122] Prepare the raw material spherical alumina particles (raw material 1 to raw material 4) described in Table 1, mix them with water, and prepare a water slurry. Regarding the mixing ratio of ion exchange water and particles when preparing the water slurry, when using raw materials 1 and 2, 200 kg of particle powder is mixed with 1000 L of water. When using raw material 3, the particle powder is set to 300 kg with respect to 1000 L of ion exchange water. When using raw material 4, the particle powder is set to 200 kg with respect to 1000 L of ion exchange water. After mixing and stirring the water slurry for about 20 minutes to 1 hour, filter it using an appropriate filter to filter the water content to about 60 to 80 wt%.
[0123] (Examples 1 to 3)
[0124] The prepared slurry was pre-frozen once at -40°C and then freeze-dried at 80°C for 24 hours while the inside of the apparatus was vacuum-degassed.
[0125] (Example 4)
[0126] The prepared slurry was air-dried at 200° C. using a jet turbo dryer manufactured by Hiraiwa Iron Works.
[0127] (Comparative Examples 1 to 3)
[0128] The prepared slurry was left in an oven without airflow and dried by a heat drying method at 230° C. for 40 hours.
[0129] (Comparative Example 4)
[0130] The slurry prepared using raw material 4 was freeze-dried under the same conditions as in Example 1.
[0131] (Comparative Example 5)
[0132] The slurry prepared using the raw material 1 was pre-frozen once at -40°C and then freeze-dried at 95°C for 24 hours while the inside of the apparatus was vacuum-degassed.
[0133] (Comparative Example 6)
[0134] The slurry prepared using the raw material 1 was air-dried at 350° C. using a jet turbo dryer manufactured by Hiraiwa Iron Works.
[0135] (Example 5)
[0136] The spherical alumina particles obtained in Example 1 were mixed with aluminum nitride particles (D50 = 30 μm) in a ratio of (weight of spherical alumina particles): (weight of aluminum nitride particles) = 90:10 to prepare a spherical alumina particle mixture A. Furthermore, the spherical alumina particle mixture A was mixed with silicone resin CY52-276A liquid manufactured by Dow Toray so that the amount of spherical alumina particle mixture A added to the resin composite composition was 90% by mass, and vacuum kneading was performed using a vacuum kneading machine "Defoam Rentaro" manufactured by THINKY to obtain a resin composite composition. The kneading conditions were pre-kneading for 15 seconds and vacuum kneading for 90 seconds. After kneading, the plastic container containing the kneaded material was placed in a water bath adjusted to 25° C. and cooled for 1 hour. 10 g of the resin composite composition was placed on an iron plate with a smooth surface and tilted 60° relative to the horizontal direction to confirm the degree of fluidity of the resin composite composition. As a result, after being tilted for 5 hours, the resin composite composition flowed for more than 15 cm, showing good fluidity.
[0137] (Example 6)
[0138] The spherical alumina particles obtained in Example 2 were mixed with boron nitride particles (D50 = 30 μm) in a ratio of (weight of spherical alumina particles): (weight of boron nitride particles) = 90:10 to prepare a spherical alumina particle mixture B. Furthermore, the spherical alumina particle mixture B was mixed with silicone resin CY52-276A liquid manufactured by Dow Toray so that the amount of the spherical alumina particle mixture B added to the resin composite composition was 90% by mass, and vacuum kneading was performed using a vacuum kneading machine "Defoam Rentaro" manufactured by THINKY to obtain a resin composite composition. The kneading conditions were pre-kneading for 15 seconds and vacuum kneading for 90 seconds. After kneading, the plastic container containing the kneaded material was placed in a water bath adjusted to 25°C and cooled for 1 hour. 10 g of the resin composite composition was placed on an iron plate with a smooth surface and tilted 60° relative to the horizontal direction to confirm the degree of fluidity of the resin composite composition. As a result, after being tilted for 5 hours, the resin composite composition flowed for more than 15 cm, showing good fluidity.
[0139] Table 2 shows the physical property values of the (dried) spherical alumina particles obtained under the various conditions.
[0140] [Table 1]
[0141] Table 1
[0142] unit Raw materials 1 Raw materials 2 Raw materials 3 Raw materials 4 Average particle size um 0.9 0.8 1.9 0.7 Specific surface area <![CDATA[m 2 / g]]> 3.2 3.3 1.6 3.4
[0143] [Table 2]
[0144]
[0145] The measuring methods of the physical property values are as follows.
[0146] (Average particle size by laser diffraction scattering method)
[0147] The laser diffraction / scattering particle size distribution measurement method is a method of irradiating a dispersion liquid in which spherical alumina particles are dispersed with laser light and obtaining the particle size distribution based on the intensity distribution pattern of the diffracted / scattered light emitted from the dispersion liquid. In the present invention, the laser diffraction / scattering particle size distribution measurement device used is "Mastersizer 3000 (manufactured by Malvern)".
[0148] (Specific surface area)
[0149] The specific surface area (BET value) was determined by applying the BET theory to the adsorption isotherm measured by the gas adsorption method (BET method). The specific surface area was measured using a specific surface area measuring instrument "Macsorb Model HM-1208" manufactured by Mountech.
[0150] (Surface residual Na)
[0151] The amount of ionic impurities attached to the surface can be measured using ion chromatography. Add 4 g of sample and 40 ml of distilled water to a centrifuge tube, cover it, and shake it thoroughly to mix. After mixing, use a centrifuge to separate the sample and sample solution. Take the sample solution and use ion chromatography to analyze sodium ions. Ion chromatography is measured using an ion chromatograph made by East Asia Medical Electronics.
[0152] (Contains Na 2 O)
[0153] 0.5 g of the sample was added to a pressurized container, 10 ml of sulfuric acid (1+3) was added and the container was covered, and then heated at 230° C. for 16 hours in a heating drying oven. The heated solution was allowed to cool, and the solution was fixed to 100 ml and measured by an atomic absorption spectrometer. In addition, sulfuric acid (1+3) refers to a solution obtained by diluting 3 volumes of pure water with respect to 1 volume of concentrated sulfuric acid.
[0154] (Cohesion)
[0155] Overlap two standard sieves with mesh sizes of 4.75 mm and 212 μm in sequence. The order of overlapping is to place the sieve with mesh size of 212 μm at the bottom and overlap it with mesh size gradually becoming larger. Place 50 g of sample on the top sieve with mesh size of 4.75 mm and set it on a vibrating sieve machine. The vibrating sieve machine used is OCTAGON200 manufactured by Endecotts. After setting the sieve, set the vibrating sieve machine to an amplitude of 5 and an oscillation time of 3 minutes. After the oscillation is completed, measure the particle weight of the particles remaining on each sieve and the particles passing through the mesh size of 212 μm. When the amount of particles on the mesh size of 4.75 mm is set as Ag, the amount of particles on the mesh size of 212 μm is set as Bg, and the amount of particles passing through the mesh size of 212 μm is set as Cg, calculate (cohesion degree) = A / (B+C)×100(%).
[0156] The above-described examples confirmed that spherical alumina particles having a low surface residual Na concentration and a low degree of aggregation can be obtained, and that a resin composite composition containing the spherical alumina particles can be obtained.
[0157] Industrial Availability
[0158] The surface residual Na concentration of the spherical alumina particles of the present invention is low, so when used as a filler, poor curing and loss of voltage resistance can be avoided. In addition, since the degree of cohesion is small, it does not need to be crushed, and the mixing (contamination) of foreign matter caused by crushing can be avoided. Therefore, as a filler, it can be suitably used in miniaturized and thin semiconductor packages, etc. Furthermore, according to the manufacturing method as one embodiment of the present invention, the spherical alumina particles can be easily manufactured. The resin composite composition containing the spherical alumina particles shows good quality and is not limited to semiconductor sealing materials, but can also be used for other purposes. Specifically, it can also be used as prepregs for printed circuit boards, various engineering plastics, etc.
Claims
1. A spherical alumina particle, The average particle size is 0.4-1.9um, and the specific surface area is 1.0-5.0m 2 / g, the surface residual Na is less than 20ppm, the Na2O content is less than 1000ppm, the agglomeration degree is less than 1.0%, and the circularity is greater than 0.
9.
2. The spherical alumina particles according to claim 1, characterized in that The alpha conversion rate is 10.0% or less.
3. A method for producing spherical alumina particles, comprising: A water slurry preparation step of mixing raw material spherical aluminum oxide with water to prepare a water slurry containing the raw material spherical aluminum oxide; and A drying step of drying the water slurry.
4. The method for producing spherical alumina particles according to claim 3, The method includes a raw material spherical alumina washing step of washing the raw material spherical alumina with water before the water slurry preparing step.
5. A resin composite composition, characterized in that: Contains the spherical aluminum oxide particles as described in claim 1 or 2.
6. The resin composite composition according to claim 5, It also contains at least one inorganic filler selected from amorphous spherical silica particles, crystalline spherical silica particles, titanium dioxide particles, magnesium oxide particles, aluminum nitride particles, boron nitride particles, barium titanate particles, calcium titanate particles, and carbon fibers.
Citation Information
Patent Citations
Spherical inorganic oxide powder, method for producing the same and use thereof
JP2008120673A
Washing treatment method and washing treatment device for powder
JP2012021710A